1998
DOI: 10.1046/j.1365-2362.1998.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylation stimulating protein (ASP) as a predictor of impaired cellular biological response to ASP in patients with hyperapoB

Abstract: A decrease in the ASP cell-surface receptor concentration is responsible for decreased ASP stimulation of TGS, and GT and may contribute to the inefficient postprandial triglyceride (TG) clearance in HASP-HB subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Thus, cells from subjects with high ASP levels were shown to have a reduced specific binding and response to ASP. 31,32 In addition, ASP levels are increased in obese diabetic subjects, and it has been suggested by Koistinen et al 12 that the metabolic disturbances in diabetes may overcome the regulatory role of ASP on lipid and glucose metabolism, again suggesting that high ASP levels indicate ASP resistance. 12 In a study of postprandial lipemia with a range of responses, higher fasting ASP predicted delayed TG clearance in both men and women.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, cells from subjects with high ASP levels were shown to have a reduced specific binding and response to ASP. 31,32 In addition, ASP levels are increased in obese diabetic subjects, and it has been suggested by Koistinen et al 12 that the metabolic disturbances in diabetes may overcome the regulatory role of ASP on lipid and glucose metabolism, again suggesting that high ASP levels indicate ASP resistance. 12 In a study of postprandial lipemia with a range of responses, higher fasting ASP predicted delayed TG clearance in both men and women.…”
Section: Discussionmentioning
confidence: 98%
“…7 In patients with cardiovascular disease, we have demonstrated that subjects with increased plasma Apo B (HyperapoB) and increased ASP are characterized by cellular resistance to the action of ASP as measured by decreased ASP cellular binding and decreased stimulation of both triglyceride synthesis (fatty acid esterification) and glucose transport. 68 Further, subcutaneous and omental adipocyte membranes from obese subjects (especially male subjects) demonstrate reduced ASP binding and affinity. 16 Thus, a high plasma ASP might be a marker for ASP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been shown that ASPmediated FFA uptake in vitro is impaired in peripheral cells of FCHL patients, suggesting a receptor defect rather than decreased ASP production. 22 Different studies, aimed at investigating the relationship between C3 and lipids, showed that fasting C3 concentrations were correlated strongly not only with lipid parameters but also with several features of the insulin resistance syndrome. 23,32 Ylitalo et al 24 also found a correlation between fasting lipids and insulin concentration with plasma ASP levels.…”
Section: Discussionmentioning
confidence: 99%